2022
DOI: 10.1038/s41598-022-16182-7
|View full text |Cite
|
Sign up to set email alerts
|

Low anti-Müllerian hormone levels are associated with an increased risk of incident early-onset vasomotor symptoms among premenopausal women

Abstract: The role of anti-Müllerian hormone (AMH) levels in incident vasomotor symptoms (VMS) is largely unknown. This study aimed to investigate the relationship between AMH levels and the development of early-onset VMS among premenopausal women. Our cohort study comprised 2041 premenopausal women aged 42–52 years free of VMS at baseline whose AMH levels were measured. VMS, including hot flushes and night sweats, were assessed using the Korean version of the Menopause-specific Quality of Life questionnaire. Early-onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A large study of 2,041 premenopausal women in Korea found that women in the lowest compared with the highest quintile of AMH prior to menopause had an increased risk of vasomotor symptoms (HR: 2.38; 95% CI: 1.84 to 3.08), suggesting a relationship between AMH and vasomotor symptoms that our study may not have power to identify. 26 As vasomotor symptoms peak in the year of the final menstrual period, it is also possible that women in the lowest AMH tertile in our study were more likely to be beyond the time of peak vasomotor symptoms at the Mid-Life visit due to their earlier age of menopause.…”
Section: Discussionmentioning
confidence: 85%
“…A large study of 2,041 premenopausal women in Korea found that women in the lowest compared with the highest quintile of AMH prior to menopause had an increased risk of vasomotor symptoms (HR: 2.38; 95% CI: 1.84 to 3.08), suggesting a relationship between AMH and vasomotor symptoms that our study may not have power to identify. 26 As vasomotor symptoms peak in the year of the final menstrual period, it is also possible that women in the lowest AMH tertile in our study were more likely to be beyond the time of peak vasomotor symptoms at the Mid-Life visit due to their earlier age of menopause.…”
Section: Discussionmentioning
confidence: 85%
“…In a cohort of 2041 premenopausal women aged 42–52 years without any VMS at baseline, the investigators reported an inverse association between quartiles of AMH and the risk for climacteric symptoms during a follow-up period of 4.4 years. More specifically, the multivariable-adjusted hazard ratio (HR) for the development of incident early onset VMS was estimated as 1.02 (95%CI: 0.78 to 1.33) compared to 2.38 (95%CI: 1.84 to 3.08), for women with AMH levels in the top as opposed to the lowest quartile [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of using AMH to assess ovarian reserve in patients who have received treatment for cancer is that there are no established cut-off values for AMH to predict the progression to menopause and the development of vasomotor symptoms. Yet diminished ovarian reserve, even without infertility or POI, likely remains an adverse effect of receiving gonadotoxic therapy and there does seem to be an independent and significant association between lower AMH levels and early onset vasomotor symptoms such that some have proposed that the onset of menopause can be predicted using a patient’s AMH and age ( NamGoung et al, 2022 , Broer et al, 2011 ). For any premenopausal patient who is planning to receive chemotherapy, and especially those who desire future fertility, an AMH level should be drawn before and after treatment to assist patients pursuing fertility treatments but also can also assist clinicians in counseling their patients on the long-term effects of their treatments.…”
Section: What Workup/evaluation Is Needed To Assess Baseline Ovarian/...mentioning
confidence: 99%